PAH clusters as interstellar very small grains. Issue Volume 15:Issue S350(2019) (April 2019) - Roser, Joseph. E.; Ricca, Alessandra
Abstract: PAH clusters are one candidate species for the interstellar "very small grains" or "VSGs", i.e., dust grains small enough to be stochastically heated and contribute to the aromatic infrared emission bands (AIBs). This possibility motivated laboratory experiments on the infrared spectroscopy of PAH clusters using matrix isolation spectroscopy. The spectral shifts due to PAH clustering in argon matrices provide clues for the AIB contribution from PAH clusters in the interstellar medium. Here we review results from a number of small PAH species, extrapolation to the much larger PAHs believed to be present in the interstellar medium, and the implications for a PAH cluster contribution to the VSG population.